Evaluation of Urban Transportation Preferences with Analytical Hierarchy Process Method - Sekmen, Fuat; Demirkol, İsa; Gökırmak, Haşmet; Gökırmak, Haşmet (Springer, 2024)
This study aims to analyze the inner-city transportation modes and rank them according to some predetermined criteria for the city of Bursa. The Analytical Hierarchical Process (AHP) method, a Multiple Criteria Decision Making (MCDM) method, was used to cre ate a general ranking for the modes of vehicles operating within the city. A total of seven criteria that afect the choice of transportation type were considered in this study. These are price, prestige, comfort, timely arrival, safety, ease of payment, and courtesy. A group of experts was consulted to determine the importance of these criteria. Safety, on-time arrival, and courtesy were the most critical factors for this analysis. Four modes, UBER, taxi, minibus, and bus, were used as alternative transportation modes. The AHP method was used to estimate weighted average scores of seven criteria for four-mode alternatives. The AHP analysis results indicate that the most preferred inner-city transportation alternative is UBER, followed by taxi, bus, and minibus
Keywords: Transportation; AHP; Transportation modes